2017
DOI: 10.18203/2320-1770.ijrcog20172563
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic hystero-laparoscopy in work-up of female infertility

Abstract: Background: Infertility is a growing concern of the society. In many cases the exact cause of infertility may not be elucidated, whether it is tubal, ovarian, uterine, or a combination of factors. This paper aims to understand the role of diagnostic hystero-laparoscopy in evaluation of cases of infertility.Methods: This prospective study included 200 infertile women and it was conducted at department of Obstetrics and Gynaecology, MGM Hospital, during the period between January 2016 to December 2016. All the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…Hence the results are comparable with the previous studies. [7][8][9] In the present study ovarian pathology was seen in 55% of the women and among this 42% of the women had polycystic ovaries which is comparable to the study by Talib W et al 6 In present study anovulatory infertility is common. 33% of the women had tubal abnormalities detected on laparoscopy which correlates with the literature that tubal factors account for 15-30% of infertility.…”
Section: Discussionsupporting
confidence: 87%
“…Hence the results are comparable with the previous studies. [7][8][9] In the present study ovarian pathology was seen in 55% of the women and among this 42% of the women had polycystic ovaries which is comparable to the study by Talib W et al 6 In present study anovulatory infertility is common. 33% of the women had tubal abnormalities detected on laparoscopy which correlates with the literature that tubal factors account for 15-30% of infertility.…”
Section: Discussionsupporting
confidence: 87%
“…In our study uterine factors responsible for infertility in 11% in primary and 0% in secondary & the results are comparable to Chaitra K et al (11) 10%in primary and 6% in secondary, Rai A et al 11.5% in primary and 6% in secondary & Mehta AV et al studies. 12,13 In our study, tubal factors were responsible for (18.4) of primary and (23%) of secondary infertility. Overall it accounted for 22% cases.…”
Section: Discussionmentioning
confidence: 49%
“…The results are comparable to Chaitra K et al 20% in primary and 8% in secondary, Rai A et al 27% primary and 8% secondary & Mehta AV et al 17% in primary and 5% secondary but however among findings of various other ovarian factors, in our study PCOS is more prevalent. [11][12][13] In hysteroscopic evaluation (Table 5) endometrial polyp was seen in 40% cases of primary and 17.4% cases of secondary infertile patient .out of 23 secondary infertile patient 34.8% had intrauterine adhesions, 8.7% had uterine septum, submucous fibroid seen in 17% cases of secondary infertile patients. Diagnosis of endometrial polyps via hysteroscopy is 94% sensitive and 92% specific.…”
Section: Discussionmentioning
confidence: 99%
“…Amrita et al, at Patna, Bihar reported tubal factor was responsible for infertility in 35.5% in her study. 13 Uterine factors constitute (16.3%) in 18 patients in present study. Commonest finding was fibroid uterus constituting to 6.7%.…”
Section: Discussionmentioning
confidence: 50%